2012
DOI: 10.1021/ie300863x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Li–Al Layered Double Hydroxides (LDHs) for Efficient Fluoride Removal

Abstract: A novel adsorbent of Li−Al layered double hydroxides (LDHs) was prepared through the precipitation of metal nitrates and further applied to remove excessive fluoride ions from water. The physical and chemical properties of synthesized materials were examined by powder transmission electron microscopy (TEM), X-ray diffraction (XRD) analysis, N 2 adsorption/ desorption analysis, and thermogravimetric analysis (TGA). The TEM results indicated that the materials synthesized via coprecipitation present a preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 40 publications
(47 reference statements)
5
46
0
Order By: Relevance
“…The divalent and trivalent anions have more effect than monovalent anions on adsorption capacity, similar results were observed in the literature for fluoride adsorption by Li/Al-LDHs [31]. This may be due to a high negative charge density of ions which were easily absorbed by the PO − ion appears to display a maximum interference for F − ion.…”
Section: Effect Of Co-anionssupporting
confidence: 85%
“…The divalent and trivalent anions have more effect than monovalent anions on adsorption capacity, similar results were observed in the literature for fluoride adsorption by Li/Al-LDHs [31]. This may be due to a high negative charge density of ions which were easily absorbed by the PO − ion appears to display a maximum interference for F − ion.…”
Section: Effect Of Co-anionssupporting
confidence: 85%
“…The percentage desorption of BSA increased with increasing desorption time. Compared with the adsorption process, the BSA desorption process was relatively fast and desorption equilibrium was attained after 2 h. The equilibrium times of desorption were approaching the equilibrium times of fluoride adsorption onto LDH materials, as previously reported . It is indicated that the BSA desorption rates were determined by interactions between anions and the surface of composites.…”
Section: Resultsmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) are a family of lamellar compounds containing exchangeable anions in the interlayer space, and have the strong intralayer bonds and weak interlayer interactions . As a natural clay mineral, they are widely used in the fields of bioseparation, catalysis, pollution control, and biomedicine . Due to the metal hydroxide layer having positive surplus charges, a large number of guest anions can be inserted into the interlayer space of LDHs through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in pH above 7 declined the percentage fluoride removal. This can be attributed to the change of the adsorbent surface charge as can be illustrated by the help of point of zero charge (pHpzc) [41]. The point of zero charge is the most significant factor utilized to illustrate variable charge surfaces in phenomenon of adsorption.…”
Section: Effect Of Phmentioning
confidence: 99%